BELAJAR ILMU NAHU DI ERA DIGITAL: PENDEKATAN MANDIRI (SELF DIRECT LEARNING) MELALUI PLATFORM INSTAGRAM - Ritonga, Ade Muhammad; Suib, Muhammad; Zaky, Ahmad (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The purpose of this research is to describe and illustrate self-directed learning of Nahwu (Arabic Grammar) through Instagram content on the accounts @nahwu.id and @nahwu_pedia, as well as to compare the two accounts. This research adopts a qualitative descriptive approach, with data collected through observation and documentation of the content available on these accounts. The results of the study indicate that the Instagram accounts @nahwu.id and @nahwu_pedia have distinct characteristics in delivering self-directed learning of Nahwu. @nahwu.id focuses on basic materials presented in a simple and minimalistic manner, making it more accessible for beginners who aim to build a solid foundation in Arabic grammar. On the other hand, @nahwu_pedia offers a broader range of materials, covering both basic and advanced topics, with visually appealing designs and interactive features such as Q&A sessions, polls, and exercises in stories. Both accounts utilize various Instagram features, such as reels for concise explanations, highlights to archive essential content, and comments to foster direct interaction with followers. These accounts are effective in supporting self-directed learning of Nahwu, albeit with different focuses. @nahwu.id is more suitable for beginners, while @nahwu_pedia caters to intermediate and advanced learners seeking interactivity and comprehensive material coverage.